(untitled) (Al-Qamar, 2022)
This study examines the domains of emotional stability among 153 school heads in five southern districts of KP, focusing on emotional awareness, emotional regulation, emotional expressivity, social competence, and stress coping. A researcher-made questionnaire was used to assess their perception levels for the above-mentioned domains of emotional stability. The questionnaire was properly validated and its reliability was recorded as 0.82. The population of the study comprised 572 school heads. The questionnaire was distributed among 235 school heads among which 153 responded properly. Most school heads (64%) responded to the high impact of stress-coping skills on their work performance. The lowest impact domain was considered emotional awareness (39%). These results highlight the need for training programs and skill development practices to enhance stress-coping capabilities in school heads. Moreover, encouraging discussion forums for emotional awareness among school heads, and creating a supportive environment for expression, feedback, and emotion management is highly recommended.